Ivabradine in treatment of symptomatic heart failure and supraventricular tachycardias in patients under six months of age - Gómez-Ganda, L.; Parramón-Teixidó, C. J.; Giralt-García, G.; Fernández-García, C.; Ferrer-Menduiña, Q.; Cabañas-Poy, M. J. (Frontiers in Pharmacology, 2025)
BackgroundAlthough heart failure (HF) and supraventricular tachycardias (SVT) are associated with high morbidity and mortality in pediatrics, especially, in children under 6 months; the efficacy of available treatments is limited, requiring the use of off-label therapies. The aim of the study is to investigate the efficacy, dosage, and safety of off-label ivabradine in patients under 6 months of age with HF or SVT.MethodsRetrospective observational study, which included patients under 6 months of age with HF or SVT who received ivabradine between January 2020 - May 2024. Demographic, clinical, and treatment-related variables were collected. Response variables were established according to indication, HF: heart rate (HR) and left ventricular ejection fraction (LVEF); SVT: HR.ResultsThirteen patients (nine women) with a median age of 1.4 (1-4) months were included. Ivabradine was discontinued in five of the seven HF patients due to resolution of HF, control of HR, and improvement of LVEF. One patient discontinued ivabradine because of bradycardia. In the SVT group, four of the seven patients discontinued ivabradine after the resolution of tachyarrhythmia and improvement of HR. Two patients experienced bradycardia but did not require treatment discontinuation. HR reduction was statistically significant in both groups. In HF, the median initial ivabradine dose was 0.06 mg/kg/day and the maintenance dose was 0.2 mg/kg/day. In SVT, the initial and maintenance doses were 0.1 mg/kg/day and 0.24 mg/kg/day, respectively.ConclusionIvabradine demonstrated favorable efficacy and safety results in patients under 6 months of age with HF or SVT.